2012
DOI: 10.1074/jbc.m111.293613
|View full text |Cite
|
Sign up to set email alerts
|

Noggin Is Novel Inducer of Mesenchymal Stem Cell Adipogenesis

Abstract: Background: Besides inhibiting osteoblast differentiation of MSC, noggin may induce adipogenesis. Results: Noggin induces adipogenic differentiation of MSC via a novel mechanism. Individuals with high BMI have elevated circulating noggin levels in plasma. Conclusion: Noggin regulates both osteoblast and adipocyte differentiation of MSC and, hence, is a master regulator of MSC plasticity. Significance: Noggin may be a novel biomarker for obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…The few studies available suggest that the effect on adipogenic differentiation of Noggin varies from cell to cell. In bone marrow MSCs, Noggin treatment promoted adipogenesis, whereas in human stromal cells, Noggin had an inhibitory effect on adipogenic differentiation if added prior to full differentiation . It has also been found that expression of Noggin is reduced or eliminated in differentiated cells, whether they are adipocytes or cardiac/skeletal myocytes, which suggests that modulation by Noggin may be most important during the early cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies available suggest that the effect on adipogenic differentiation of Noggin varies from cell to cell. In bone marrow MSCs, Noggin treatment promoted adipogenesis, whereas in human stromal cells, Noggin had an inhibitory effect on adipogenic differentiation if added prior to full differentiation . It has also been found that expression of Noggin is reduced or eliminated in differentiated cells, whether they are adipocytes or cardiac/skeletal myocytes, which suggests that modulation by Noggin may be most important during the early cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this effect has been reported to be independent of BMP activity, raising the question as to whether Noggin can regulate additional cell signaling pathways (Sawant et al, 2012).…”
Section: Nogginmentioning
confidence: 98%
“…Adipose-derived stem cells (ASCs) are mesenchymal stem cells (MSCs) that are obtained from abundant adipose tissue [8,9]. High fat mass is caused by an increase in the size (hypertrophy) and number (hyperplasia) of adipocytes.…”
Section: Introductionmentioning
confidence: 99%